I bambini dell’Altro. Adozioni internazionali tra il Burkina Faso e l’Italia - Concetti, Martina (Antropologia Pubblica, 2018)
International adoption, because of its very nature, must be considered from multiple spatial perspectives. In this work two areas were taken into account: Burkina Faso and Italy. The study focuses on the relational and emotional dynamics interrelated with the Italian parents, the Burkinabé children and their crossing of the two territories. The analysis of the dossiers of the children adopted through ARAI-Regione Piemonte shows that the main causes of abandonment could be traced: incest, alleged mental illness of the mother and found children. These are the children’s stories that will then be integrated by the adoptive parents in their personal family history. Structuring itself day after day and reconstructing its daily routine, the adoptive family manages to become familiar with itself and to recognize itself as such.